Dysphoria mundi / Paul B. Preciado. - Preciado, Paul B. (Fitzcarraldo Editions, 2025)
In 'Dysphoria Mundi', Paul B. Preciado has written a mutant text assembled from essays, philosophy, poetry and autofiction that captures a moment of profound change and possibility.